Efektifitas Kearsipan Dalam Meningkatkan Pelayanan Administrasi di Desa Bulu-Bulu Kecamatan Tonra Kabupaten Bone - Andi Amitya Resty Dwiyanti (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
This study aims to determine the effectiveness of records related to administrative services in Bulu-Bulu Village. This research uses a quantitative approach. The results of the study revealed that in general 42.85% of respondents rated archive management as very good, 42.85% good and 14.28% bad. Archive management so far is going well. In fact, the human resources in the archiving department at the Bulu-Bulu village office are very limited, because the archivists do not have basic knowledge about the archiving department. The low quality of management services is caused by several factors such as: B. unclear procedures, confusing technical and administrative requirements, the completion time that exceeds the specified time, the lack of transparency of the costs incurred and the distance of the place of residence from the place of residence. village office. It can be concluded that (1) the effectiveness of archives in improving administrative services in Bulu-Bulu Village, Tonra District, Bone Regency, namely the procedure for making archives is good, but there is no method used that facilitates management by making it faster and more efficient. (2) The factors that encourage and hinder the improvement of administrative services are the public's appreciation of public service users, the clarity of technical and administrative requirements, and the knowledge of staff about the administrative service industry.